1999
DOI: 10.1021/jp990912r
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding between Acetone and Silica Gel, as Studied by NMR

Abstract: 13C NMR spectra and relaxation parameters (T 1 H, T 1 C, T 1 ρ H, T CH) were measured via CP-MAS and DP-MAS techniques as a function of acetone loading level in acetone/SiO2 samples at 25 °C. T 1 H and T 1 ρ H values were also measured via 29Si CP-MAS experiments. Peak positions and relaxation parameters are averaged by rapid exchange between different acetone interaction sites on the surface. The data were analyzed in terms of a surface equilibrium of adsorbed acetone units between hydrogen-bonding and non-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 49 publications
3
38
0
Order By: Relevance
“…The role of silanols in the reaction can be explained by the fact that carbonyl compounds adsorb on the surface of silica via hydrogen bonding. [26,[51][52][53][54][55][56] We confirmed this interaction by measuring NMR spectrum of 13 C-labeled acetone set in contact with non-functionalized MSN (Figure S6), which exhibited a downfield shift of the carbonyl carbon signal compared to that of neat acetone (~213 ppm versus 206 ppm). Our earlier solid-state NMR and theoretical studies demonstrated that surface silanols on silica also interact with the amine functionalities.…”
Section: Cooperative Effects Of the Supportmentioning
confidence: 79%
“…The role of silanols in the reaction can be explained by the fact that carbonyl compounds adsorb on the surface of silica via hydrogen bonding. [26,[51][52][53][54][55][56] We confirmed this interaction by measuring NMR spectrum of 13 C-labeled acetone set in contact with non-functionalized MSN (Figure S6), which exhibited a downfield shift of the carbonyl carbon signal compared to that of neat acetone (~213 ppm versus 206 ppm). Our earlier solid-state NMR and theoretical studies demonstrated that surface silanols on silica also interact with the amine functionalities.…”
Section: Cooperative Effects Of the Supportmentioning
confidence: 79%
“…Solid state NMR has long been used to identify and characterize the structures of small organic molecules adsorbed onto catalytic surfaces [10][11][12], argon matrices [13], silica and alumina surfaces [14][15][16]. There similarly exist a number of solid state NMR pulse techniques capable in principle of reporting the structures of surface-adsorbed proteins.…”
Section: Nmr Methods For the Study Of Protein Structure At Biomateriamentioning
confidence: 99%
“…These models are derived from the full set of 1,000 models. Alignment of the models in the figure was based on root-mean-square deviation calculation of segments (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and (33)(34)(35)(36)(37)(38) between the 8 models. Table 1 31 P-31 P nearest neighbor distances lying within a sphere of radius 6 Å for the 004 crystal plane in in monoclinic HAP.…”
Section: Figmentioning
confidence: 99%
“…The role of silanols in the reaction can be explained by the fact that carbonyl compounds adsorb on the surface of silica via hydrogen bonding. [26,[51][52][53][54][55][56] We confirmed this interaction by measuring NMR spectrum of 13 C-labeled acetone set in contact with non-functionalized MSN ( Figure S6), which exhibited a downfield shift of the carbonyl carbon signal compared to that of neat acetone (~213 ppm versus 206 ppm). Our earlier solid-state NMR and theoretical studies demonstrated that surface silanols on silica also interact with the amine functionalities.…”
Section: Cooperative Effects Of the Supportmentioning
confidence: 78%
“…[48][49][50][51][52][53] Even though homogeneous catalysts are known to exhibit higher selectivity and superior kinetics, heterogeneous catalysts are advantageous with respect to easy product separation from reaction mixtures and reuse until loss of activity. 54 Moreover, the ability to confine the catalyst inside the mesopores provides a greater specificity to a reaction by introducing size and shape Fukuoka and co-workers showed higher TOF using sulfonic acid functionalized mesoporous silica than Amberlyst-15 for hydrolysis of sucrose and starch to glucose and fructose.…”
Section: Mesoporous Silica Supported Organocatalystmentioning
confidence: 99%